Pengaruh Hak Cipta terhadap Inovasi dan Kebebasan Berkreasi di Era Digital - Ni Putu Windi Adnyani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Amidst the rapid development of digital technology today, copyright plays a complex role as an instrument for protecting works and at the same time as a potential inhibitor of innovation. Protection of exclusive rights granted by the copyright protection system aims to provide economic incentives or financial benefits to the creator. However, in practice, it often creates limitations on creative freedom, especially in the context of derivative works, remixes, parodies, and other creative uses that are developing rapidly in the digital realm. This study aims to examine how the copyright legal system, both normatively and implementatively, affects the scope of movement of creative actors in producing innovation. Through a normative legal approach with a review of international and national literature, this study found that copyright protection is too strict and has the effect of freezing reactivity, especially if it is not balanced with clear fair use provisions. However, on the other hand, loose regulations will also risk ignoring the moral and economic rights of the original creator. Thus, a balance is needed between the protection of individual rights and the public interest within the framework of a legal system that is adaptive and inclusive of digital culture. The study recommends strengthening open licensing frameworks such as Creative Commons, as well as updating national copyright policies to ensure that legal systems do not hinder, but rather encourage, the growth of innovation and creative expression in the digital age.